SOCIAL CRITICISM MEANING OF PUTRA NUSANTARA SONG LYRICS SHAGGY DOG FEAT IWA K. - Aa Qonaatun (Journal of English Language Teaching and Literature (JELTL), 2019)
Music is one of the communication media to convey implied messages. Music is also a cultural means that is present in society as a construction of social reality as outlined in the form of song lyrics. The most prominent social music functions are found in the lyrics. An ideal song lyrics do not only contain ideas to entertain but also have moral or idealistic messages and have the power of constructive social criticism. One of the musicians who dared to create songs about social problems was the band Shaggydog who released a song titled Putra Nusantara. The purpose of this study was to determine the meaning of social criticism on the song Putra Nusantara using the Teun A. Van Djik approach covering the dimensions of the text, dimensions of social cognition and dimensions of social context. The text dimension will analyze the macro structure, superstructure and micro structure, then discuss it into the dimensions of social cognition and social context dimensions to find the meaning of criticism of the song. After analyzing the micro structure, which is based on syntactic, semantic, stylistic and rhetorical structures, it turns out that there are many clauses that are incoherent with one another or based on the superstructure, in the temple scheme many meanings are even lost. However, based on the overall meaning, the song implies to state officials who do not pay attention to proper education for children. However, based on social cognition, the song cannot be proven true if the school is expensive. Macro structure can be seen from the relationship of the text with what is in the minds of listeners. Then, in the social context, there are a lot of satirical expressions that can be known meaning based on the social context.